Insilico and Electron Microscope Study about Attachment of Mesenchymal Stem Cell Derived from Stromal Vascular Fraction to Scaffold (Bovine Bone Cancellous, Hydroxyapatite-Calcium Sulphate, Calcium Phosphate) - Panji Sananta (Journal of Global Pharma Technology, 2019)
Objective: Insilico study using molecular docking with Hex had already surpassed all of the other previous approach in assessment of molecular binding to scaffold. The combination of insilico study to investigate the molecular binding to scaffold and electron microscope to assess the population density of adipocyte derivative stem cells by measuring the number of cluster cells could show the inter cell communication between adipocyte derived stem cell and scaffold. The aim of this study is to prove the attachment of mesenchymal stem cell (MSC) from stromal vascular fraction (SVF) to scaffold.Methods: The research is true experimental research using molecular docking with HEX version 8.0. Electron microscope used to measure the density and number of cluster cells of adipocyte derivative stem cells.Results: The strongest bound to scaffold is between MSC from SVF to hydroxyapatite in both receptor which was Integrin Alpha V to Hydroxyapatite which need a total energy of -89.24 (J/Mol) and Integrin Beta 2 to Hydroxyapatite which need a total energy of -177.8 (J/Mol). The highest impact obtained from hydroxyapatite-calcium phosphate with an average value of 12.66 cluster cells counting per 100 µm2 scaffold material observed by electron microscope.Conclusion: This study showed that MSC from SVF could attach to scaffold with stronger binding between Integrin Alpha V and Integrin Beta 2 to hydroxyapatite. From microscope electron study we can prove that MSC can make a cluster cell in those scaffolds with hydroxyapatite-calcium sulphate having the biggest cluster cell counting.Keywords: Hydroxyapatite; Integrin Alpha V; Integrin Beta 2; Mesenchymal stem cell; Scanning electron microscope; Stromal vascular fraction.